Utilization of low rank coal as oxidation catalyst by controllable removal of its carbonaceous component - Nurhadi M.; Efendi J.; Lee S.L.; Mahlia T.M.I.; Chandren S.; Ho C.S.; Nur H. (Taiwan Institute of Chemical Engineers, 2023)
Calcination; Catalyst activity; Catalysts; Catalytic oxidation; Hydrogen; Hydrogen peroxide; Oxidation; Peroxides; Styrene; Sulfonation; Titanium oxides; Transition metals; Active site; Carbonaceous components; Cobalt oxides; Low rank coals; Oxidation catalysts; Oxidation of styrene; Coal